The 2020 Coronavirus Pandemic and Its Corresponding Data Boon: Issues With Pandemic-Related Data From Criminal Justice Organizations. (November 2021) - Wallace, Danielle; Walker, Jason; Nelson, Jake; Towers, Sherry; Eason, John; Grubesic, Tony H.
Public organizations, including institutions in the U.S. criminal justice (CJ) system, have been rapidly releasing information pertaining to COVID-19. Even CJ institutions typically reticent to share information, like private prisons, have released vital COVID-19 information. The boon of available pandemic-related data, however, is not without problems. Unclear conceptualizations, stakeholders' influence on data collection and release, and a lack of experience creating public dashboards on health data are just a few of the issues plaguing CJ institutions surrounding releasing COVID-19 data. In this article, we detail issues that institutions in each arm of the CJ system face when releasing pandemic-related data. We conclude with a set of recommendations for researchers seeking to use the abundance of publicly available data on the effects of the pandemic.